REPLICATION MIXED CROPPING SYSTEMS FOR URBAN LAND UTILIZATION IN SIDOARJO REGENCY, EAST JAVA - Susilo, Achmadi; Thohiron, Mochamad; Suryaningsih, Dwie Retna; Wilujeng, ⁠Sukian; Sulthoni, ⁠Muhammad Hasan Askari (Yayasan Education and Social Center, 2025)
This community service program aims to replicate the mixed cropping system as an innovation in land use development in the urban area of Sidoarjo Regency, East Java. With high pressure on land availability due to urbanization, the productive use of yard land is crucial to support local food security and community well-being. The program was implemented from May to June 2025, involving 10 locations in several sub-districts with various combinations of fast-growing vegetables and horticultural crops. The activity approach included land identification, outreach, technical training, planting implementation, and intensive mentoring. The results showed a significant increase in land productivity and active community participation in intercropping land management. Mixed cropping has proven effective in increasing crop diversification while maintaining micro-ecosystem balance by reducing the use of chemical pesticides. Despite constraints such as limited water supply and maintenance time, efficient irrigation solutions and time management can be an alternative. This model has the potential to be replicated in other urban areas with similar characteristics and can serve as a reference for developing spatial planning policies based on local food security. This activity contributes to community empowerment and sustainable development in urban areas.